Pengembangan E-book Cerita Bergambar Berbasis STEAM Untuk Meningkatkan Kemampuan Sains Anak di Taman Kanak-Kanak - Mastuinda; Yaswinda (Universitas Pendidikan Ganesha, 2023)
The low ability of early childhood science is due to the need for more use of appropriate media for the child's developmental stage. This study aims to develop a learning media as an e-book with illustrated stories to test its validity and effectiveness in improving children's science skills in Kindergarten. This research is included in the type of development research by applying the Borg and Gall model. The subjects of this study consisted of 3 experts in validation and 38 children for the product trial class. The data collection method used was a questionnaire with research instruments in the form of observation sheets of children's science abilities, material expert instruments, language, and media. Data from the material validation test results obtained a percentage of 80% Valid category, Language validation 100% Very Valid category, and media validation 97.33% very valid category. The small group trials were 78.65%, and the moderate class trials were 85.73 in the very effective category. So the development of STEAM-based picture story e-books is feasible and effective for improving children's science skills in Kindergarten. The implications of this research can add to the variety of digitalization media in early childhood education, which can motivate and attract children's learning interests.